KEPEMIMPINAN YANG MENCIPTAKAN BUDAYA ORGANISASI ATAU BUDAYA ORGANISASI YANG MENYUKSESKAN KEPEMIMPINAN? - Rozikin, Mochammad; Muslim, Abd. Qadir (Jurnal Likhitaprajna, 2019)
The success of an organization, both engaged in business and social fields must payattention to the cultural and leadership variables in the organization. The two variablesare also inseparable and interdependent, even have the same value, so it is said thatseeing the leadership of an organization is the same as seeing the culture that exists inthe organization. This study aims to determine whether culture influences the success ofleadership or leadership that creates organizational culture. This study used a qualitativeapproach to data collection techniques by identifying library sources related to the conceptof leadership and organizational culture. Analysis of the data used was library research orcontent analysis. The results showed that there were two dichotomies of a theory thatinsisted on strengthening the results of his research. The first is to believe thatorganizational culture influences the leadership style and success of a leader is leading hisorganization. The second stream was known as the group of critics said that organizationalleadership has a strong influence on the birth of organizational culture so thatorganizational culture depends on who the leader is. Therefore, we must not clash thesetwo understandings to find which is the most correct, because these two understandingshave the basis and results of research that have been done. Keywords: culture, leadership, organization